The Nepean Dyspepsia Index: Translation and Validation in Indonesian Language - I Gede Arinton; Pugud Samudro; Soewignjo Soemohardjo (The Indonesian Society for Digestive Endoscopy, 2006)
Background: Dyspepsia is an important health problem from economic and quality of life point of view. However, to date, there has not been specific instrument of quality of life to evaluate patients with dyspepsia specially design in Indonesian language. The Nepean Dyspepsia Index (NDI) is a reliable and valid instrument regarding quality of life in patients with dyspepsia and had been validated in Australia, Germany, Italy and Netherlands. Objective: To report translation of NDI in Indonesian language and validation in Indonesian patients with dyspepsia and also evaluate the possibility of its use in subjects who speak Indonesian language. Methods: NDI was translated into Indonesian language. The amount of 49 subjects with a clinical diagnosis of dyspepsia according to the inclusion and exclusion criteria were recruited. Collection of data included demographic data, physical and laboratory examination. All subjects were asked to complete translation of NDI. Reliability analysis was evaluated by a-Cronbach’s and test-retest. Since dyspepsia has no gold standard, validity was evaluated using factor analysis. Result: Reliability of the questionnaire was good, a-Cronbach’s and interclass correlation coefficient were found to be 0.70 respectively and Kaiser-Meyer-Olkin value was found to be 0.64, suggesting that all items were appropriate to measure. Conclusion: translated NDI in Indonesian language can be used in dyspepsia, patients who understand Indonesian language. Keywords: dyspepsia, disease-related quality of life, the Nepean Dyspepsia Index, reliability, validity